2003
DOI: 10.1211/0022357022007
|View full text |Cite
|
Sign up to set email alerts
|

Single oral dose study of two isosorbide-based aspirin prodrugs in the dog

Abstract: The objective of this study was to compare two aspirin prodrugs, isosorbide diaspirinate (ISDA) and a nitroaspirin (ISMNA), with aspirin in terms of effects on dog platelet function after administration of a single oral dose. Groups of six dogs were administered ISDA (2 mg kg -1 ), ISMNA (4 mg kg -1 ) or aspirin (2 mg kg -1 ). Blood was sampled at 1, 2, 4, 8, 12 and 24 h postdosing and evaluated for capacity to generate post-clotting thromboxane (TX)B 2 . The aggregation response to arachidonic acid (AA) (100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
4
13
0
Order By: Relevance
“…As expected, the results of our study showed a significant difference in serum TXB 2 concentration between both groups of samples, 1098 ± 346 g/l (incubation at 37 C for one hour) versus 550 ± 257 g/l (incubation at room temperature) for one hour. Serum TXB 2 concentrations in both groups of samples showed marked intra-and inter-individual variations, which is in accordance with previously reported results (Gilmer et al 2003;Yamanaka et al 1993).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…As expected, the results of our study showed a significant difference in serum TXB 2 concentration between both groups of samples, 1098 ± 346 g/l (incubation at 37 C for one hour) versus 550 ± 257 g/l (incubation at room temperature) for one hour. Serum TXB 2 concentrations in both groups of samples showed marked intra-and inter-individual variations, which is in accordance with previously reported results (Gilmer et al 2003;Yamanaka et al 1993).…”
Section: Discussionsupporting
confidence: 93%
“…1. Serum thromboxane B 2 , in two groups of samples; one was incubated at 37 ºC for one hour, the second was incubated at room temperature for one hour is the most frequently used means of evaluating COX inhibitors mainly because this approach reduces variability due to sampling, which profoundly affects direct measurement of highly unstable TXA 2 (Blain et al 2002;Brideau et al 1996;Gilmer et al 2003;Lees et al 2004;Patrignani et al 1997;Van Hecken et al 2000). TXA 2 is normally converted to its stable product TXB 2 (Hamberg et al 1975).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations